2019
DOI: 10.1186/s12884-019-2338-z
|View full text |Cite
|
Sign up to set email alerts
|

Husbands involvement in birth preparedness and complication readiness in Axum town, Tigray region, Ethiopia, 2017

Abstract: Background Worldwide, around 289,000 maternal mortalities occur each year from complications related to pregnancy and childbirth. In Ethiopia, the maternal mortality rate is among the highest in the world. This is mainly contributed by the three delays. Husbands’ involvement in birth preparedness and complication readiness can significantly reduce these delays. Therefore, it is important to know what, currently, is the husbands view regarding knowledge of key danger sign and involvement about birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 12 publications
7
35
2
Order By: Relevance
“…This is in line with the conclusions in several studies that show the role of husband/partner in providing support for a woman's health behavior [30--33]. Some other studies actually involve a husband to be able to improve a woman's health status through actively better health behaviors [34][35].…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with the conclusions in several studies that show the role of husband/partner in providing support for a woman's health behavior [30--33]. Some other studies actually involve a husband to be able to improve a woman's health status through actively better health behaviors [34][35].…”
Section: Discussionsupporting
confidence: 89%
“…In this systematic review and meta-analysis, we measure male involvement using three domains such as involvement during antenatal care (ANC), during delivery, and post-partum period. Accordingly, eight studies [24][25][26][28][29][30][31][32] which reported antenatal care involvement were included in the pooled analysis of male involvement during ANC. In this meta-analysis, the proportions of pooled male involvement during antenatal care were found to be 41.14% [95% CI (23.68-58.60)] (Fig.7).Whereas, male involvement during delivery and post-partum period was found unfortunately similar with the pooled proportion of 45.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…We found Six studies [25,26,28,29,31,32] that describe about male involvement during delivery and post-partum periods from three regions of Ethiopia(Oromia, Amhara, and Tigray). Similarly there was high heterogeneity for delivery and post-partum involvements (I-squared= 98.9%, p≤ 0.0001).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…The total sample size of the included studies in this review were 4210, ranging among studies included from 125 in Nepal [42] to 592 in Ethiopia [43]. Five of the included studies were from Asia [10,42,[44][45][46], seven studies from Africa with the majority from Ethiopia [43,[47][48][49][50][51][52]. Additionally, all studies included in the review were cross-sectional study designs (Table 1).…”
Section: Study Inclusionmentioning
confidence: 99%
“…The I 2 test result showed heterogeneity (I 2 = 94.95%, p<0.001) and Egger's test (p-value < 0.01). Clean clothes being made ready for both the baby and the mother observed to be the lowest 45.6% in Nepal [42] and the highest 86.5% in Ethiopia [47] (Table 1). In the sub-analysis the heterogeneity test showed the presence of heterogeneity (I 2 = 94.4%, p<0.001) and publication bias (Egger's test p-value < 0.001).…”
Section: Review Ndingsmentioning
confidence: 99%